Temperature stresses in cylindrical ignot at heating in circular furnaces - Ju. S. Postolnik; V. I. Timoshpolskij; Ju. N. Zinchenko; D. N. Andrianov (Литьë и металлургия, 2003)
There is received for the first time solution of the problem of nonlinear thermomechanics (heat conduction and thermoelasticity) for the case of heating of cylinder ingots in the counter-current regime. Analysis of the received solution allowed to establish more low level of thermo-stressed state of ingots in contra-flow as compared with direct-flow.